2013
DOI: 10.1007/s00217-012-1905-6
|View full text |Cite
|
Sign up to set email alerts
|

Modification of functional quality of raw myofibril preparation obtained from water-washed mechanically recovered chicken meat

Abstract: The aim of this study was to evaluate the effect of enzymatic modification of poultry myofibril preparation on its selected functional properties, that is, solubility of proteins, polymerisation rates of myosin and actin, thermodynamic properties and texture. The myofibril preparation (MP) from mechanically recovered chicken meat, produced by washing and separation of fat and connective tissue, was subjected to the action of the transglutaminase preparation added at 0.3 % for a period ranging from 0.5 to 24 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
2
11
0
2
Order By: Relevance
“…This seems to be corroborated by the thermodynamic analysis (DSC) of the myofibril preparation modified by transglutaminase. In the case of samples with the addition of enzymatic preparation, we can see a certain decrease in the T1 (for myosin) temperature by approximately 1°C (after 5-h modification) in relation to the control sample (Stangierski et al 2013). The effect of the transglutaminase addition on thermal properties of proteins was similar to the results of investigations conducted by Aktaş and Kiliç (2005) on myofibril preparations obtained from beef.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…This seems to be corroborated by the thermodynamic analysis (DSC) of the myofibril preparation modified by transglutaminase. In the case of samples with the addition of enzymatic preparation, we can see a certain decrease in the T1 (for myosin) temperature by approximately 1°C (after 5-h modification) in relation to the control sample (Stangierski et al 2013). The effect of the transglutaminase addition on thermal properties of proteins was similar to the results of investigations conducted by Aktaş and Kiliç (2005) on myofibril preparations obtained from beef.…”
Section: Resultssupporting
confidence: 82%
“…However, it is not a drastic reduction of these values. This was also observed in (n=6) studies using differential scanning calorimetry (DSC) (Kazemi et al 2011;Stangierski et al 2013) and rheological analyses (Stangierski et al 2014).…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…; Stangierski et al . ). Patented method of producing gluten‐free bread and treating pale soft exudative meat with transglutaminase were also issued (Milkowski and Sosnicki ; Diowksz et al .…”
Section: Introductionmentioning
confidence: 97%
“…The addition of MTGase to food products can improve their quality. Nielsen (1995), Dickinson (1997), Kuraishi et al (1998) and Motoki and Seguro (1998) identified the products of the MTGase reaction, i.e., ε-(γ-glutamyl) lysyl cross-links between food proteins, and cross-linking different food proteins with MTGase such as milk proteins, egg proteins, raw myofibril preparation, myosin and soy protein isolates were reported (Motoki and Seguro 1998;Guo et al 2013;Stangierski et al 2013). Patented method of producing gluten-free bread and treating pale soft exudative meat with transglutaminase were also issued (Milkowski and Sosnicki 1999;Diowksz et al 2013).…”
Section: Introductionmentioning
confidence: 99%